KERUGIAN NEGARA DALAM PEMBERIAAN PINJAMAN DANA BERGULIR BAGI KOPERASI SIMPAN PINJAM - Jacob Hattu (Faculty of Law, Universitas Pattimura, 2016)
Cooperative is one of the pillars of economic effort that plays a very important role and is a vital nation economic tool, because it can reach the lives of all people, especially small communities in rural areas. To support the Cooperative as an economic organization that empowers small communities, the government provides a revolving fund program. In pratiknya repayment of the loan does not run well so that occur troubles especially bad loans, while the funds that have been rolled must be accounted by the cooperative, the inability of cooperatives in managing the loan funds raises the state money can not be returned and resulted in the loss of the state and it must be in account Criminally.